2019
DOI: 10.7554/elife.43882
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell expression profiling reveals dynamic flux of cardiac stromal, vascular and immune cells in health and injury

Abstract: Besides cardiomyocytes (CM), the heart contains numerous interstitial cell types which play key roles in heart repair, regeneration and disease, including fibroblast, vascular and immune cells. However, a comprehensive understanding of this interactive cell community is lacking. We performed single-cell RNA-sequencing of the total non-CM fraction and enriched (Pdgfra-GFP+) fibroblast lineage cells from murine hearts at days 3 and 7 post-sham or myocardial infarction (MI) surgery. Clustering of >30,000 singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

45
502
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 457 publications
(609 citation statements)
references
References 98 publications
45
502
3
Order By: Relevance
“…These include fibroblasts (Pdgfra, Col1a1), pericytes (Pdgfrb, Vtn), smooth muscle cells (SMCs; Acta2, Myh11), Schwann cells (Plp1, Kcna1), endothelial cells (Pecam, Ly6c1), macrophages (Fcgr1, Csf1r), and other immune cell populations 6 (granulocytes, B cells, T cells and NK cells). A subset of fibroblasts (Fibroblast-Wif1) showed distinct gene expression patterns including active Wnt signaling and specific expression of Wif1, in line with our previous report [4] and the findings of Farbehi et al [5]. Additional less well-characterized cell populations included CMs (Ttn, Myh6), epicardial cells (Msln, Upk3b), lymphatic endothelial cells (Lyve1, Cldn5) and endocardial cells (Npr3, Cytl1) ( Figure 1B-D).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These include fibroblasts (Pdgfra, Col1a1), pericytes (Pdgfrb, Vtn), smooth muscle cells (SMCs; Acta2, Myh11), Schwann cells (Plp1, Kcna1), endothelial cells (Pecam, Ly6c1), macrophages (Fcgr1, Csf1r), and other immune cell populations 6 (granulocytes, B cells, T cells and NK cells). A subset of fibroblasts (Fibroblast-Wif1) showed distinct gene expression patterns including active Wnt signaling and specific expression of Wif1, in line with our previous report [4] and the findings of Farbehi et al [5]. Additional less well-characterized cell populations included CMs (Ttn, Myh6), epicardial cells (Msln, Upk3b), lymphatic endothelial cells (Lyve1, Cldn5) and endocardial cells (Npr3, Cytl1) ( Figure 1B-D).…”
Section: Resultssupporting
confidence: 89%
“…Previous large-scale single cell transcriptomic studies exploring cardiac cellular diversity have failed to profile key cardiac cell populations including CMs [3][4][5][6] due to a reliance on dropletbased sequencing approaches that are incompatible with large cell isolation. Moreover, extraction of CMs from rodent hearts typically requires retro-aortic perfusion with proteases to liberate cells from the extracellular matrix; this is a relatively time-consuming process that has limited applicability for cell preparation in transcriptomic studies [7].…”
Section: Resultsmentioning
confidence: 99%
“…However, both populations of CF are characterized by different markers, most probably because of the low number of Mki67 + CF included in the scRNA-seq study, and the reporter mice used. Interestingly, Faberhi et al described 9 subpopulations of PDGFRα + CF with a similar transcriptomic profiles that our subpopulations of Col1α1-GFP + CF at 7dpi 30 . However, our data indicate that CF that express Pdgfrα are contained within Col1α1-GFP + CF ( Fig.…”
Section: Discussionsupporting
confidence: 84%
“…CTHRC1 is a secreted protein that has the ability to inhibit collagen matrix synthesis through inhibition of TGF-β signaling 20,21,33 and that appears as a top marker gene for IRCF. Although expression of Cthrc1 has been previously identified as a potential marker for activated CF after MI in mice 9,30 and humans 29 , the longer follow-up in our study (up to 30dpi) may explain why it was not previously identified as a key player in the cardiac repair process. According to our results, expression of Cthrc1 peaks at 14dpi and decreases thereafter.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation